Numerical modeling of mesoscale atmospheric processes of transport of impurities in the vicinity of the city of kirov - Shatrov, Anatoly Victorovich; Shvarts, Konstantin Grigor'evich (Computational Continuum Mechanics, 2010)
A quasitwo-dimensional model for impurity propagation from an anthropogenic source has been developed with regard to the thermal heterogeneity of an underlying surface in the vicinity of a large industrial city. The equations are derived using a three-dimensional hydro-thermodynamic model of mesoscale processes in the lower atmosphere. Boundary conditions and coefficients of the model are determined by parameterization techniques. The results of numerical calculations are presented. Calculations were implemented with the use of parallel algorithms on the cluster supercomputer of the Vyatka State University. It is shown that the vortex motion is formed in the lower part of the atmosphere over the city under the influence of a non-uniform horizontal temperature gradient. The perturbed wind field strongly influences the character of impurity distribution in the vicinity of the heat source.
Keywords: advection; transport of impurity; two-dimensional model; mathematical and numerical simulation